FACTORS ASSOCIATED WITH CHILDHOOD CHRONIC MALNUTRITION DURING THE FIRST 12 MONTHS OF LIFE IN CHILDREN FROM A PERUVIAN COHORT - Morales-Cahuancama, Bladimir (2025)
Objective. To determine the factors associated with chronic child malnutrition (CCM) in two Peruvian re-gions: Huancavelica and Loreto. Materials and methods. We analyzed four repeated cross-sectional evaluations nested in a prospective cohort of children treated in primary healthcare facilities. Data was collected on the characteristics of the child, the mother and the household, including anthropometric information, breastfeeding, complementary feeding, and socioeconomic conditions. A generalized linear model was used to calculate the prevalence ratios (PR) for each of the four quarterly evaluations of the cohort (3rd, 6th, 9th and 12th months). Results. Factors such as male sex, bottle feeding and the use of polluting fuels were associated with a higher risk of CCM, on the other hand, having six or more prenatal check-ups and being a beneficiary of the JUNTOS program acted as protective factors. Mothers who did not speak Spanish as their native language, who worked or studied, or who had limited participation in family decisions, were also at higher risk of CCM. In addition, we identified unexpected associations, such as food insecurity acting as a protective factor, reflecting possible biases or confounding effects. Conclusions. Our findings highlight the importance of addressing inequalities in prenatal care, dietary practices, and mothers’ participation in household decision-making to prevent CCM in vulnerable contexts.